2016
DOI: 10.1016/j.fgb.2016.10.003
|View full text |Cite
|
Sign up to set email alerts
|

The botrydial biosynthetic gene cluster of Botrytis cinerea displays a bipartite genomic structure and is positively regulated by the putative Zn(II)2Cys6 transcription factor BcBot6

Abstract: a b s t r a c tBotrydial (BOT) is a non-host specific phytotoxin produced by the polyphagous phytopathogenic fungus Botrytis cinerea. The genomic region of the BOT biosynthetic gene cluster was investigated and revealed two additional genes named Bcbot6 and Bcbot7. Analysis revealed that the G + C/A + T-equilibrated regions that contain the Bcbot genes alternate with A + T-rich regions made of relics of transposable elements that have undergone repeat-induced point mutations (RIP). Furthermore, BcBot6, a Zn(II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
101
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(108 citation statements)
references
References 97 publications
5
101
0
2
Order By: Relevance
“…While Bcstc1/Bcbot2 and Bcstc5/Bcaba5 are now identified as the key genes for the biosynthesis of botrydial and ABA respectively, the role of the other Bcstc genes remains unknown. Most B. cinerea strains produce botrydial in significant amounts in standard culture conditions, i.e., 7–10 µg ml −1 (Reino et al ., ; Pinedo et al ., ; Porquier et al ., ), but the other sesquiterpenes are often below the detection level. In comparison, there is an apparent redirection of FPP‐derived metabolism in the strain ATCC58025, resulting in a significant overproduction of ABA.…”
Section: Discussionmentioning
confidence: 66%
“…While Bcstc1/Bcbot2 and Bcstc5/Bcaba5 are now identified as the key genes for the biosynthesis of botrydial and ABA respectively, the role of the other Bcstc genes remains unknown. Most B. cinerea strains produce botrydial in significant amounts in standard culture conditions, i.e., 7–10 µg ml −1 (Reino et al ., ; Pinedo et al ., ; Porquier et al ., ), but the other sesquiterpenes are often below the detection level. In comparison, there is an apparent redirection of FPP‐derived metabolism in the strain ATCC58025, resulting in a significant overproduction of ABA.…”
Section: Discussionmentioning
confidence: 66%
“…The overall TE content of C. higginsianum (7%) is comparable to that reported previously for C. graminicola (12.2%) and C. orbiculare (8.3%) [13, 91] and other phytopathogenic fungi with similar sized genomes such as Z. tritici (16.7%), S. sclerotiorum (12.9%), B. cinerea (3.7%) and V. dahliae (12.3%) but is strikingly less than in L. maculans (33.3%), Blumeria graminis f. sp. hordei (76.4%) and Melampsora larici-populina (51.7%) [6, 8, 25, 92, 93]. LTR elements are the most abundant TEs in C. higginsianum , as reported in other fungi, e.g.…”
Section: Discussionmentioning
confidence: 89%
“…The polyketides 2-7 and 9-15 were also isolated and identified by comparison of their spectroscopic data with those of authentic samples. 19 Six new compounds (16)(17)(18)(19)(20)(21) were isolated from the fractions of medium polarity and purified by further chromatography including HPLC. The 1 H and 13 C NMR spectra suggested that they possessed sesquiterpenoid structures.…”
Section: Resultsmentioning
confidence: 99%
“…In the HMBC spectrum (see Table S3, ESI †) there were correlations between H-2 and C-3, C-4 and C-8 and between H-15 and C-1. Thus the structures of 16-18 were presilphiperfolan-8α,10β,14-triol (16), 8α,14-dihydroxypresilphiperfolan-10-one (17) and 8α,10β,14-trihydroxypresilphiperfol-1-ene (18).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation